PENGARUH SERTIFIKASI GURU DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA GURU AKUNTANSI SMA DI KOTA CILEGON - Anis Fuad Salam; Suwiro Heriyanto (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2018)
The purpose of this study is to know: 1) the effect of certification on the performance of accounting teachers in Senior High School (SMA) Kota Cilegon; 2) the influence of career development on the performance of high school accounting teachers in Cilegon City; 3) the influence of certification and career development together towards the performance of accounting teachers in SMA Kota Cilegon. The method used is a survey of all high school accounting teachers in Cilegon City. Number of samples counted 48 people. Based on the research results can be concluded: (1) There is a significant influence between teacher certification with job satisfaction of accounting teachers in Cilegon City; (2) there is a significant influence between career development with job satisfaction of accounting teacher in Cilegon City; and (3) there is a significant influence between teacher certification and career development on accounting teacher accounting satisfaction in Cilegon City.